Four views on the Book of Revelation - Pate, C. Marvin, 1952- (Grand Rapids, MI Zondervan, 1998)
Contents : A preterist view of Revelation / Kenneth L. Gentry Jr; An idealist view of Revelation / Sam Hamstra Jr; A progressive dispensationalist view of Revelation / C. Marvin Pate; A classical dispensationalist view of Revelation / Robert L. Thomas.
Keywords: Bible. N.T. Revelation -- criticism, interpretation, etc